Effect of Drilling Waste on Public Health in Obite, Rivers State Nigeria - Benson-Ubochi Chibueze (IIARD INTERNATIONAL JOURNAL OF GEOGRAPHY AND ENVIRONMENTAL MANAGEMENT, 2026)
This study examined the environmental and public health implications of drilling-waste contamination in Obite Community, Ogba/Egbema/Ndoni Local Government Area, Rivers State, Nigeria, using an interdisciplinary approach integrating environmental sampling, laboratory analysis, spatial exposure assessment, and household health surveys. Soil and water samples were collected across four distance-based exposure zones (0–500 m to 1,501–2,000 m from the disposal site). Soil analysis revealed markedly elevated heavy metal and hydrocarbon concentrations proximate to the dumpsite; lead ranged from 40.1 mg/kg in Zone A to 13.1 mg/kg in the control zone, while Total Petroleum Hydrocarbons reached 845 mg/kg near the site compared with 225 mg/kg in the control. Water quality in Zone A was characterised by acidic pH (5.5–5.7), elevated turbidity, high total dissolved solids, lead concentrations up to 0.34 mg/L, and total coliform counts of up to 295 CFU/100 mL — all exceeding recommended standards. A structured survey of 320 respondents revealed a clear exposure-response gradient in health outcomes. Mean reported symptoms declined from 5.4 in Zone A to 1.5 in the control zone, with annual hospital visits decreasing from 3.8 to 1.1. Regression analysis confirmed significant associations between soil TPH and respiratory symptoms (β = 0.67, R² = 0.72) and between water contamination and gastrointestinal illness (β = 0.61, R² = 0.64). The findings demonstrate that drilling-waste disposal has significantly degraded local environmental quality and is associated with elevated health risks among nearby residents, underscoring the urgent need for improved waste management, continuous monitoring, and provision of safe water in Niger Delta oil-producing communities.